Intrusi Air Laut di Kecamatan Padang Utara - sispandi saputra; Ahyuni ahyuni; Endah Purwaningsih (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
Some parts of the coast of Padang City are found to have brackish ground water whose distribution is getting wider. The purpose of this study is to map the distribution of sea water intrusion in the District of North Padang. Intrusion distribution is mapped based on the value of electrical conductivity (DHL) with the criteria for the level of salinity as determined by Simoen (2000: 23). Sampling was carried out in three villages in the North Padang Subdistrict namely Air Tawar Barat Subdistrict, Ulak Karang Utara and Ulak Karang Selatan with a purposive random sampling technique or random samples as needed, namely 30 samples of residents' well water using EC Meters to measure electrical conductivity and GPS to determine the coordinates of the location of research samples. The data analysis technique used is quantitative descriptive. The results showed that there were wells that were indicated to have experienced sea water intrusion along the coast of North Padang District, which was about 16.6% of the 30 samples tested in the field with four points entered into the classification of brackish water with an Electrical Conductivity value of 832-874 (µmhos / cm) and one point included in the classification of salt water with an Electrical Conductivity value of 3686 (µmhos / cm). Keywords: Electric conductivity, Sea water intrusion.